Cooperating Teachers’ Best Practices for Mentoring #2: Social Support - Heather R. Nesbitt; Debra M. Barry (EDIS)
Social support is most often considered the care of the student teacher’s problems. This publication will break down the major areas of social support and provide real-world examples of how to implement them during the internship. Written by Heather R. Nesbitt and Debra M. Barry, and published by the UF/IFAS Department of Agricultural Education and Communication; 3 pp. https://edis.ifas.ufl.edu/wc420